Impact of the unconventional extraction on antioxidants and antimicrobial characteristics of hibiscus and olive leaves extracts - Abdel-Aziz R.E. El-Hadary; Ayat M.A. Abulmakarm; A.M. Sulieman; Gehan A. El-Shorbagy; Alaa S. Mohamed (Heliyon)
The antioxidant extracts considered a very important food additive which promoting the protection of lipid and prolong the shelf life of food products. The aim of this investigation was decrease the time of extraction of hibiscus leaves extract (HLE) and olive leaves extract (OLE) from 48 h to only 6 h without reducing efficiency of these extracts. HPLC assay, scavenging radical activity by DPPH˙ (IC50), inhibition lipid peroxidation by both β-Carotene/Linoleic Acid Bleaching (βCB) and Thiobarbituric Acid Reactive Substances (TBARs) assays, antibacterial and antifungal activities measured for different concentrations of ethanolic extracts by conventional extraction (CE) and difference in pressure extraction (DPE) methods, and the results shown a considerable in mean difference (P < 0.05) between the mean values of all extracts of same raw material and also extraction methods, a positive effect for the extracts by DPE method. The absolute ethanolic extracts registered high efficiency (P < 0.05) and the olive leave extract was the highest (273.5 ± 1.5 mg GAE g−1 of dried extract, 18.1 ± 0.8 μg mL−1 to IC50, 86.2 ± 0.2 % to βCB, 91.16 ± 0.45 % to TBARs, 34.94 ± 0.7 (P < 0.05) to inhibitor the growth of Staphylococcus aureus, and 1.25 ± 0.5 (P < 0.05) to diameter the colony of Aspergillus ochraceus). The results also showed that DPE extraction not only reduced the extraction time to 12.5 % (P < 0.05) (from 48 h to only 6 h), but also registered higher efficiency in antioxidant and antimicrobial activity compared with the conventional extraction method.